Acoustical imaging. Volume 30 - André, Michael P.; Jones, Joie P.; Lee, Hua 1952-.; SpringerLink (Online service). (Dordrecht [Netherlands] Springer, 2011)
The International Symposium on Acoustical Imaging is a unique forum for advanced research, covering new technologies, developments, methods and theories in all areas of acoustics. This interdisciplinary Symposium has been taking place every two years since 1968. In the course of the years the proceedings volumes in the Acoustical Imaging Series have become a reference for cutting-edge research in the field. In 2009 the 30th International Symposium on Acoustical Imaging was held in Monterey, CA, USA, March 1-4. Offering both a broad perspective on the state-of-the-art as well as  in-depth research contributions by the specialists in the field, this Volume 30 in the Series contains an excellent collection of forty three papers presented in five major categories: Biomedical Imaging Acoustic Microscopy Non-Destructive Evaluation Systems Analysis Signal Analysis and Image Processing Audience Researchers in medical imaging and biomedical instrumentation experts.
Preface. Part I BIOMEDICAL IMAGING Performance of a Method to Standardize Breast Ultrasound Interpretation Using Image Processing and Case-Based Reasoning -- High Resolution Ultrasonic Method for 3D Fingerprint Recognizable Characteristics In Biometrics Identification -- Ultrasonic Detection of Metastases in Dissected Lymph Nodes of Cancer Patients -- Measurement of Mechanical Properties of Soft Tissue with Ultrasound Vibrometry -- Vector Doppler Method Based on an Automatic Transverse Angle Tracking Procedure -- Proposal for Blood-Flow Imaging by Contrast Echo Using Counter-Crossed Beams -- Inverse Scattering Theory -- Inverse Scattering Results -- Multiple Scattering Contribution to Trabecular Bone Backscatter -- ULA-OP:  A Fully Open Ultrasound Imaging/Doppler System -- The Use of Quality Metrics in Ultrasonic Strain Imaging -- Applying Echoes Mean Frequency Shift for Attenuation Imaging in Tissue. Part II ACOUSTIC MICROSCOPY Visualization of Microvessels in Skin by Three-Dimensional Ultrasound Microscope      -- Technique for Visualization of Anisotropy of Biomedical Tissue by Shear Wave Acoustic Microscopy -- High Frequency Ultrasound Imaging of Cartilage-Bone Complex -- Ultra-High Resolution Thin Film Thickness Delineation Using Reflection Phase-Sensitive Acoustic Microscopy -- Signal Processing for Time-Lapse Cell Imaging with Vector-Colntrast Scanning Acoustic Microscopy -- Acoustic Microscopy Study of Properties and Microstructure of Synthetic and Natural Fiber Composite Materials. Part III non-destructive evaluation A  Defect Localization Procedure Based on Warped Lamb Waves -- Second Harmonic Detection Generated from Fastened Bolt.-  In-line Ultrasonic Array System for Monitoring Dynamic of  Coating Forming by Cold Spray Process -- An Experimental Comparison of Thermographic and Acoustical Methods for Evaluation of Layered Structures -- Acoustic Microscope Inspection of Cylindrical Butt Laser Welds. Part IV systems analysis Intracardiac Forward-Looking Ultrasound Imaging Catheters Using Capacitive Micromachined Ultrasonic Transducers -- Conformal Ultrasound Imaging System -- Air-Coupled Vibrometry -- A Hybrid Kirchoff Migration Direction-of-Arrival Method for Underwater Imaging of Complex Objects Using Sparse Sensor Arrays -- Multi-View Acoustic Sizing and Classification of Individual Fish -- Acoustic Image Models for Obstacle Avoidance with Forward-Looking Sonar -- Underwater Acoustical Imaging and Sensing Systems for Homing, Docking, Navigation and Collision Avoidance. Part V signal analysis and image processing Resolving the Location of Acoustic Point Sources Scattered Due to the Presence of a Skull Phantom -- Reflection and Scattering of Acoustical Waves from a Discontinuity in Absorption -- Automatic Regions of Interest Segmentation for Computer Aided Classification of Prostate TRUS Images -- Determination of B/A of Biological Media by Measuring and Modeling Nonlinear Distortion of Pulsed Acoustic Wave in  Two-Layer System of Media -- A Consideration of Multi-Dimensional Simulation of Nonlinear Acoustic Wave Propagation Using the CIP Method -- A Study of Similarity Measures for In Vivo 3D Ultrasound Volume Registration -- Image Quality Improvement Performance Using the Synthetic Aperture Focusing Technique Data -- Expectation Maximization for Joint Deconvolution and Statistics Estimation -- Particle Swarm Optimization for In Vivo 3D Ultrasound Volume Registration -- Gauge Theory Formulation of Acoustical Imaging -- High Resolution Pulse Compression Imaging Using Super Resolution FM-Chirp Correlation Method (SCM) -- Medical Ultrasound Image Deconvolution -- Numerical and Physical Modeling of Tomography Process  Based on Third-Order Nonlinear Acoustical Effects.  EPILOGUE Subject Index Author Index.
Electronic reproduction.
Keywords: Acoustic imaging -- Congresses; Acoustic holography -- Congresses; Ultrasonic imaging -- Congresses; Electronic books